2020
DOI: 10.12788/jhm.3422
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Use of Postdischarge Intravenous Antibiotic Therapy for Children

Abstract: Children with complicated appendicitis, osteomyelitis, and complicated pneumonia have historically been treated with postdischarge intravenous antibiotics (PD-IV) using peripherally inserted central catheters (PICCs). Recent studies have shown no advantage and increased complications of PD-IV, compared with oral therapy, and the extent to which use of PD-IV has since changed for these conditions is not known. We used a national children’s hospital database to evaluate trends in PD-IV during 2000-2018 for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The marked reduction in PICC placement should be celebrated but not met with complacency; current data continue to reveal wide variation in care patterns and opportunities for care improvement among children with osteomyelitis. 9,27 The rapid practice change observed in this study emphasizes the importance of longitudinal measurement of low-value services on a population basis. Regular measurement is needed to establish improvement targets and prioritize deimplementation initiatives.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…The marked reduction in PICC placement should be celebrated but not met with complacency; current data continue to reveal wide variation in care patterns and opportunities for care improvement among children with osteomyelitis. 9,27 The rapid practice change observed in this study emphasizes the importance of longitudinal measurement of low-value services on a population basis. Regular measurement is needed to establish improvement targets and prioritize deimplementation initiatives.…”
mentioning
confidence: 84%
“…Fenster et al, using the Pediatric Health Information System database, identified a decrease in the percentage of patients with osteomyelitis treated with postdischarge intravenous antibiotics from 61% in 2000 to 22% in 2018. 9 Yi et al identified a decrease in PICC rates for children with osteomyelitis and septic arthritis from 56% in 2009-2012% to 26% in 2012-2015 at 2 large, freestanding children's hospitals. 7 The lower rates of PICC placement at the conclusion of the study period in the National Inpatient Sample data, as compared with those observed in freestanding children's hospitals, may be related to differential acuity between these samples, although further investigation into the drivers of these differences may be informative.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were corroborated in another study that revealed a consistent reduction in the use of intravenous antibiotics on discharge in children with osteomyelitis over an 18-year period. 37 The mounting evidence of improved outcomes with early transition to oral antimicrobial therapy demonstrates that despite the rise in acute osteomyelitis in children, national emphasis on value-driven clinical practices and quality improvement initiatives like "Choosing Wisely" may be associated with PICC placement reduction. 38 We found that overall LOS remained stable for acute osteomyelitis hospitalizations at 4.6 days, which is similar to the previous study in which researchers used the Kids' Inpatient Database.…”
Section: Figurementioning
confidence: 99%
“…
In this edition of the Journal of Hospital Medicine, Fenster and colleagues evaluate the trend of postdischarge intravenous (IV) antibiotic therapy for children with osteomyelitis, complicated pneumonia, and complicated appendicitis. 1 Children requiring prolonged antibiotic therapy were historically discharged home with a peripherally inserted central catheter (PICC) for IV antibiotics. Recent studies suggest that treatment failure occurs uncommonly, and that oral antibiotics are as effective as those administered intravenously.
…”
mentioning
confidence: 99%